Illegal FAD Installations: Criminal Law Approaches in Indonesian Philippine Waters - Albri Labaka (Universitas Negeri Semarang, 2026)
This study aims to explain that fish aggregators (FADs) are fishing aids (ABPI) that are an integral part of fishing vessels. The illegal installation of FADs by Filipino fishermen in the EEZ area is contrary to the 1982 UNCLOS, which states that Indonesia has jurisdiction to take action under Law No. 45 of 2009 on fisheries, using normative research methods, conceptual approaches, and legislative approaches. The study results show that the judge in the trial of the case complies with UNCLOS 1982 Article 73 paragraph (3), which is the basis for fines without imposing imprisonment unless there is a prior agreement between Indonesia and the Philippines. As a result, punishing the perpetrator does not have a deterrent effect, so other actors appear to commit the same crime. The weakness of the Fisheries Law is that it does not regulate the application of additional sanctions. Therefore, with the basic idea of a double-track system, in the future, it is necessary to revise the Fisheries Law with the formulation of additional sanctions in the form of ship sinking sanctions, social work sanctions, and the concept of maximizing fines based on social welfare, with a multi-example system.